Electrocatalysis and Electrocatalysts for a Cleaner Environment Fundamentals and Applications - Eudora Khotseng, Lindiwe (IntechOpen, 2022)
This book discusses electrocatalysis and electrocatalysts for energy, water electrolysis, water treatment, CO2 conversion, and green chemistry. It reviews various electrocatalysts and their properties and electrochemical performances. The first section of the book covers topics in direct alcohol fuel cells including Pt-based electrocatalysts as non-carbon electrode support materials and the development of electrocatalysts for direct methanol fuel cells. The second section of the book covers various topics in electrocatalysis and electrocatalysts for a cleaner environment, including electrocatalysts for the conversion of CO2 to valuable products and SYNGAS, electrocatalysts for water electrolysis, and much more.